Master-Slave Arm Heterogeneous Mapping With Link Pose Constraint in Teleoperation System - Ziwen Li; Enzheng Zhang; Bin Zhai; Bingchen Li (IEEE Access, 2022)
In order to solve the problem in master-slave heterogeneous teleoperation systems, which is that the inverse solution of robot cannot be achieved when the mapped wrist joint exceeds the reachable space of robot wrist joint, a master-slave heterogeneous mapping method based on link pose constraint is proposed. The link pose constraint means that the position and orientation of robot hand link are the same or similar to that of exoskeleton hand link. In the proposed method, the link pose constraint is used in an exoskeleton-based heterogeneous teleoperation system to realize consistent mapping between the exoskeleton and robot hand link inside wrist joint reachable space, and to realize effective inverse solution and consistent mapping of the end effector (EE) outside the reachable space. A simulation was performed by using the proposed method. The simulation results show that the proposed method can effectively realize the mapping between the exoskeleton and robot in the reachable space of robot EE. The teleoperation experimental setup was constructed by using the developed exoskeleton and an industrial robot, and the verification experiments of the proposed mapping method were performed. The experimental results indicate that the position error of the proposed heterogeneous mapping method is 0.48 mm. The experimental results demonstrate that the proposed mapping method can effectively realize master-slave heterogeneous mapping and realize continuous motion control of the teleoperation system, which satisfies the application requirements of human-robot integration, robot skill enhancement, and robot skill learning.